2000
DOI: 10.1021/ma0013004
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Model Hydrophobic Alkali-Swellable Emulsion Associative Thickeners

Abstract: Diffusion coefficients of hydrophobically modified alkali-swellable (HASE) associating polymers (APs) in aqueous solution were measured using pulsed gradient spin-echo (PGSE) nuclear magnetic resonance (NMR). HASE APs consist of a copolymer of methacrylic acid and ethyl acrylate to which hydrophobic “sticker groups” are attached through a poly(ethylene oxide) (PEO) “spacer arm”. Two series of HASE APs were investigated:  one in which the length of the hydrophobic alkyl chain was varied (C x E35) and another in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 60 publications
4
18
0
Order By: Relevance
“…By increasing the hydrophobicity of the macromonomer and the length of the PEO spacer chain of the macromonomers, the aggregation number of the hydrophobic junction increases. This was also confirmed by the self‐diffusion coefficients as determined from pulsed‐gradient NMR 9…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…By increasing the hydrophobicity of the macromonomer and the length of the PEO spacer chain of the macromonomers, the aggregation number of the hydrophobic junction increases. This was also confirmed by the self‐diffusion coefficients as determined from pulsed‐gradient NMR 9…”
Section: Introductionsupporting
confidence: 59%
“…After full neutralization, HASE polymer backbone possesses a polyelectrolyte character and solubilizes in water, while the hydrophobic groups associate to form aggregates in solution. Dynamic light scattering and pulsed‐gradient NMR of HASE solutions revealed that the apparent particle sizes or the diffusion coefficients are independent of pH, when the pH values of the solution exceed 7 8,9. After full neutralization of MAA segments, the polymer backbones behave as polyelectrolytes, where the ionic strength of the solution could strongly influence the association mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For dilute HASE solution, dynamic light scattering (DLS), fluorescence spectroscopy, and pg‐NMR, potentiometric and conductometric titrations revealed that the solution behavior of HASE polymers is extremely sensitive to pH 3, 4, 21, 22. With the addition of a base, HASE latex first swells and then dissolves into water.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophobically modified alkali‐soluble emulsion (HASE) polymers have received considerable attention in recent years 6–20. Some studies on the thermal behavior of associative polymers have been reported previously,21–28 but detailed studies on the HASE system are scare 19, 29.…”
Section: Introductionmentioning
confidence: 99%